Sosialisasi Sejarah Bank Perkreditan Rakyat (BPR) Dan Bank Perkreditan Rakyat Syariah (BPRS) Kepada Alumni Pondok Al-Iman Yang Berada Di Palembang - Meriyati Meriyati; Agus Hermanto (AKM, 2021)
Rural Banks are bank financial institutions, which accept deposits only in the form of time deposits, savings, and / or other equivalent forms and channel funds as an RB business. The People's Credit Institution originated in the Dutch colonial period in the 19th century, with the formation of the Village Lumbung, Village Bank (BD), Bank Tani (BT), and Bank Dagang Desa (BDD), with the aim of helping farmers, employees and laborers to releasing themselves from the trap of moneylenders (loan sharks) who are said to provide loans with high interest rates. With the issuance of Law no. 7 concerning Banking of 1992 (Law No. 7/1992 concerning Banking) provided a clear legal basis as a type of bank other than commercial banks. According to Law no. 7/1992 concerning Banking Non-bank financial institutions that have obtained a business license from the minister of finance may adjust their business activities as a bank.